Income inequality in the uptake of environmentally friendly products - Martina Maglicic; Vítor V. Vasconcelos (iScience)
Summary: The uptake of environmentally friendly products is unequal and income-dependent. Whether solar panels or electric vehicles, lower income groups are often locked out of the benefits they offer. Worse, policies encouraging the adoption of environmentally friendly products have replicated or even exacerbated inequalities. We experiment with analytical and agent-based models to examine mechanisms driving this inequality trap and explore policy solutions. Considering economic factors and social desirability aspects of green products, we compare adoption across income quartiles. Our findings indicate higher-income groups are much more sensitive to social desirability, including environmental awareness and peer and status effects, while lower-income groups are primarily concerned with financial constraints. Additionally, social tipping points can either enhance or hinder adoption, depending on the level of economic inequality. Without a targeted approach addressing the financial barriers of lower-income groups alongside community-wide interventions achieving a just energy transition will remain a challenge.